Oxidative esterification of renewable furfural on cobalt dispersed on ordered porous nitrogen-doped carbon. Issue 6 (15th January 2021) - Yin, Defeng; Zheng, Yanxia; Yang, Lixi; Li, Shuyue; Zhu, Daqing; Guo, Yafei; Zuo, Cuncun; Li, Yuchao; Huang, Haofei; Wang, Ming
Abstract : Catalytic oxidative esterification of furfural to methyl 2-furoate with cobalt-dispersed N-doped ordered porous carbon. Abstract : A series of highly dispersed cobalt-based catalysts on N-doped ordered porous carbon (Co-NOPC) were synthesized using the sacrificial-template method. MCM-41, ZSM-5 and SBA-15 were employed as hard templates with 2, 2′-bipyridine as the ligand. The physical and chemical properties of the Co-NOPC catalyst were characterized by Raman, XRD, SEM, TEM, EDX, ICP, BET, XPS. Co-NOPC had been proven to be a highly efficient catalyst for oxidative esterification of furfural (FUR) to methyl 2-furoate without alkaline additives. Catalytic performance was correlated to the dispersed cobalt, porous structure and specific surface area. The relationship between oxygen activation and the strong interaction of cobalt and pyridine nitrogen were confirmed by XPS. Catalytic performance enhancement mechanisms were correlated with the redistribution of electrons at the interface between carbon material and cobalt atoms through the molecular dynamics method and a reaction mechanism was also proposed. The optimized catalysts showed outstanding catalytic activity and stability and no obvious decrease in activity was found after 6 cycles with 99.6% FUR conversion and 96% methyl 2-furoate selectivity.